Associations among plasma ptau181, tau PET, and amyloid PET in a community‐based study during midlife. (20th December 2022) - Lao, Patrick J.; Simoes, Sabrina; Banjoko, Michael B.; Benavides, Andrea; Lippert, Rafael; Berroa, Joncarlos; Igwe, Kay C; Schupf, Nicole; Mayeux, Richard; Manly, Jennifer J; Brickman, Adam M.
Abstract: Background: The amyloid‐tau‐neurodegeneration (AT(N)) research framework uses a biomarker definition of Alzheimer's disease (AD); neuroimaging has been the in vivo gold standard, but plasma‐based measures are becoming more widely available yet need to be characterized earlier in the life course and AD continuum, as well as in representative samples. Our objective was to understand how plasma measures of ptau181 correspond with PET‐derived measures of amyloid and tau in middle age. Methods: In the ongoing Offspring Study of Racial and Ethnic Disparities in Alzheimer's Disease, participants (n=61; 61±6, 52‐79 years old, 67% women, 14±4 years of education, 10% Non‐Latinx White/25% Non‐Latinx Black/65% Latinx) underwent measures of amyloid (weighted average Florbetaben SUVR in Thaal phase regions) and tau (average MK‐6240 SUVR in Braak stage I; SIMOA‐based plasma ptau181). Amyloid‐positivity was determined at >1.25 SUVR and tau‐positivity was determined at >2 SD above the mean SUVR in an independent sample of cognitively unimpaired individuals. General linear models tested associations among plasma ptau181, tau PET, and amyloid PET. Results: Fifteen percent were amyloid‐positive while five percent were tau‐positive. Ptau181 was not associated with PET‐based tau burden (R=‐0.18, p=0.17). Amyloid burden increased with age (R=0.37, p=0.003). PET‐based tau burden increased with amyloid (R=0.29, p=0.02), but not with age (R=0.16, p=0.22). Conversely, ptau181 increased with amyloid (R=0.26, p=0.04) and with age (R=0.25, p=0.05). Conclusions: A temporal discrepancy between plasma and PET‐based tau, particularly in a sample of mostly amyloid‐ and tau‐negative middle‐aged adults, may explain the lack of association between ptau181 and tau PET. However, both plasma and PET‐based tau were associated with elevated amyloid burden, which is thought to be necessary for the spreading of pathological tau in AD. Prior studies suggest that associations between plasma ptau181 and tau PET are stronger and shift from early Braak stage regions to late Braak stage regions further along the AD continuum. Therefore, it is important to understand the utility of plasma ptau181 in the context of age and disease stage.